A simple and effective method to culture ciliated protozoans as a starter diet for marine finfish larvae - Mukai, Yukinori; Salam, Nurul Syuhada; Mohammad Noor, Normawaty; Kadowaki, Shusaku (2016)
Infusoria play an important role in microbial food chains. Infusoria are the microscopic single celled animalcules belonging to Class, Ciliata and Phylum, Protozoa. They are smaller in size than SS rotifers, soft bodied and highly nutritious, making them an ideal starter diet for early stage fish larvae. In tropical regions, grouper and snapper species are cultured in fish farms. Infusoria will be suitable live feed for these fish larvae, how-ever there are a limited number of studies about infusoria culture method. This study was conducted to determine optimum salinity to culture infusoria. In this study, infuso-ria were cultured following Kitani’s (1989) method. Fish meal was made by small dried anchovies (TL 40–60 mm) by a general food processor. Vegetables (Chinese cab-bage) were cut into small pieces (1–2 cm). Fish meal (0.025%/water volume) and vege-tables (0.5%/water volume) were put into 0, 10, 15, 20, 25 and 30 ppt fresh and saline water in 3 liter aquaria. Many types of infusoria were observed in fresh water group. Less number species of infusoria were observed in saline water groups. The density of infusoria in saline water showed no significant difference among different salinities. In the saline water groups, Euplotes sp. with the size of 60-80 μm was observed, and this species would be good candidate as live feed for marine finfish larvae.